Barriers and facilitators to adopting health-promoting lifestyles in patients with psoriasis in China: a qualitative study using the COM-B and SEM - Xing, Liyuan; Yu, Huiqian; Wang, Sisi; Huang, Shuya; Liu, Hongwei; Song, Jinghui (Frontiers in Public Health, 2025)
BackgroundPsoriasis is an inflammatory skin disease that places a heavy burden on patients and society. Lifestyle can affect the occurrence and progression of psoriasis and its associated comorbidities.ObjectivesTo explore facilitators and barriers to health-promoting lifestyles among patients with psoriasis using the capability, opportunity, motivation behavior (COM-B) model and the Social Ecological Model.MethodsA descriptive qualitative study was conducted using semi-structured interviews with 16 patients recruited via a WeChat group of Psoriasis Patients' Home. Data were collected and analyzed using content analysis in NVivo software (version 14).ResultsAt the individual level, barriers included limited knowledge and awareness, excessive dietary restrictions, symptom burden, difficulty changing habits, ineffective behaviors, enjoying life in time, self-awareness of controllable conditions, food temptation, and inappropriate self-image; facilitators were disease knowledge, healthy diet attention, avoidance of side effects of medicine, effective behavioral change, proactive information seeking, self-feeling of aggravating skin lesions by bad habits, improved body image, self-pleasure, and overall health promotion. At the interpersonal level, barriers were social contact needs, while facilitators included peer and family support and patient role models. At the organizational/community level, barriers were work and life pressure and unhealthy workplace eating, whereas facilitators were community network support. At the societal level, barriers were stigmatization and lack of disease-specific health promotion guidance.ConclusionsThis study highlights the multi-level factors influencing health-promoting lifestyles among patients with psoriasis and underscores the need for interventions that enhance individual capability and motivation while fostering supportive social and environmental contexts.